2020
DOI: 10.1088/1674-1056/ab7224
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of memory characteristics by employing a charge trapping layer with combining bent and flat energy bands*

Abstract: Designed Zr x Si1−x O2 films with combining bent and flat energy bands are employed as a charge trapping layer for memory capacitors. Compared to a single bent energy band, the bandgap structure with combining bent and flat energy bands exhibits larger memory window, faster program/erase speed, lower charge loss even at 200 °C for 104 s, and wider temperature insensitive regions. The tunneling thickness together with electron recaptured efficiency in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The TER was stable at 1.4×10 4 after more than 2 months, which showed that the proposed device has a robust performance. [12,45] Figure 3(b) shows the endurance test of the FTJ over 1000 cycles. After 1000 cycles, the TER remained above 1.4 × 10 4 , indicating good endurance of the device.…”
Section: Resultsmentioning
confidence: 99%
“…The TER was stable at 1.4×10 4 after more than 2 months, which showed that the proposed device has a robust performance. [12,45] Figure 3(b) shows the endurance test of the FTJ over 1000 cycles. After 1000 cycles, the TER remained above 1.4 × 10 4 , indicating good endurance of the device.…”
Section: Resultsmentioning
confidence: 99%